Human Capital Learning And Development System A Knowledge Management Approach - Liew, Tze Hui (2001)

(untitled)
In order to capitalize knowledge management effectively, a system named as Human Capital Learning and Development System (HCLDS) was carried out us a mediator to enhance human capital Iearning and continuously improvement efforts. HCLDS is an application system developed using Lotus Notes R5 technology, therefore this project is hardly rely on the technology promoted and supported by Lotus to carried out the system's prototype. Furthermore, this project is carried out based on the selfsourcing-prototyping methodology. As a knowledge management system, HCLDS is highly supporting human capital collaboration, and of course, capture and deliver of knoewledge. Moreover, HCLDS also considerably fulfilling the requirements of the ten principles of knowledge management and some others basic requirements for knowledge management system. Finally, this project predicted some future challenges of knowledge management system and some considerations for the development of the future project.